PERSEPSI WARGA BELAJAR TERHADAP PEMBELAJARAN DI PKBM MITRA RIAU JAYA CEMERLANG PEKANBARU - Ali Pamuji; Titi maemunaty; Widiastut ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study was to determine the perceptions of learners towards learning in CLC Mitra Jaya Cemerlang Riau Pekanbaru included either. This study is a descriptive study with a quantitative approach, and to use questionnaires with 65 questions a number of items.The population in this research is the study of all citizens CLC Package C in Riau Mitra Jaya Cemerlang Pekanbaru with the number 53 and the study sample as many as 30 people.The sampling technique is random sampling, where samples were taken from the population. The instruments are used in research on Citizen Perception Study Of Learning CLC Mitra Jaya Cemerlang Riau Pekanbaru, with indicators: Learning Program, Tutor, Civil Learning, Learning Support, Nursing Learning, Yeast Learning and Learning Outcomes.The results showed perceptions of learners towards learning in CLC Mitra Jaya Cemerlang Riau Pekanbaru good category. Of the seven indicators is the dominant learning program on equal education with a score 0,929 variants rhitung value of 0.638 and life skills education with a score of 0.889 variant rhitung value of 0.619.Keywords: Perception, Citizens Learning, CLC Mitra Jaya Cemerlang Pekanbaru Riau.